2007
DOI: 10.1038/sj.ijo.0803587
|View full text |Cite
|
Sign up to set email alerts
|

General and visceral adiposity in black and white adolescents and their relation with reported physical activity and diet

Abstract: Background: Excess body fat accumulation may begin in youth and is linked with increased risk of cardiovascular disease. Examination of physical activity (PA) and diet behaviours predictive of adiposity may help target efforts to reduce chronic disease risk. Objective: We hypothesized that energy intake (EI) from fat, vigorous PA (VPA), and their interaction would predict body fat percentage (%BF) and visceral adipose tissue (VAT) in youth and that sedentary behaviours and intake of dairy, fruit, vegetable and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
59
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 47 publications
8
59
0
Order By: Relevance
“…Indeed, recent projects that have measured body composition (rather than body weight) have generally found that fatter youths tend to ingest less energy than leaner youths. 4,7 One explanation for this counter-intuitive finding is that fatter youths under-report their energy intake more than leaner youths. This formulation requires that we assume that fatter youths eat more in the face of data that do not support the assumption, hardly an appropriate scientific attitude.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Indeed, recent projects that have measured body composition (rather than body weight) have generally found that fatter youths tend to ingest less energy than leaner youths. 4,7 One explanation for this counter-intuitive finding is that fatter youths under-report their energy intake more than leaner youths. This formulation requires that we assume that fatter youths eat more in the face of data that do not support the assumption, hardly an appropriate scientific attitude.…”
Section: Introductionmentioning
confidence: 81%
“…11,12 This is consistent with the findings that fatter youths watch more TV, as a surrogate for sedentariness, than leaner youths. 4 Especially noteworthy results have been obtained from recent studies that distinguished moderate PA (3-6 METS) from vigorous PA (46 METS); the breakpoint between moderate and vigorous PA is approximately the difference between brisk walking and jogging-running. 13,14 These studies have shown that the amount of time spent in vigorous PA explained more of the variance in body fatness than did lower intensities of PA.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Pearson' s correlation coefficient was first used to assess the correlations of adiposity, adipokines, and markers of inflammation with potential confounding factors, including Tanner stage, physical activity, birth weight, SES, dietary fat, and sugar-sweetened soft drink and potassium intake. [9][10][11][12]27,28 Only related confounding variables were included in the analyses.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…However, recent research has found that vigorous PA is associated with lower adiposity, while moderate PA is not (for example, StallmannJorgensen et al 4 ). What can account for this finding?…”
mentioning
confidence: 99%